POLYMORPHIC TRANSFORMATION OF TITANIUM DIOXIDE CAUSED BY HEAT TREATMENT OF PROTONIC LEPIDOCROCITE TITANATE - Hari Sutrisno; Sunarto Sunarto (Universitas Gadjah Mada, 2010)
The polymorphic phases of titanium dioxide were successfully prepared by heat treatments of protonic lepidocrocite titanate, H0.54Ti1.8650.135O4·0.5H2O at various temperatures. The prepared powders were characterized with EDX (Energy Dispersive X-ray), Scanning Electron Microscopy (SEM), X-rays Diffractometer (XRD), Raman Spectroscopy, and High Resolution Transmission Electron Microscopy (HRTEM). The effect of calcination temperature on the phase structure and morphology of the heated samples was investigated. The research indicated that the protonic titanate, H0.54Ti1.8650.135O4·0.5H2O ( = vacancy), lost the interlayer water by being heated up to 200 °C to produce a dehydrated phase, H0.54Ti1.8650.135O4. Above 300 °C, the dehydrated phase, H0.54Ti1.8650.135O4, completely transformed to TiO2(B) and anatase was obtained as pure phase at 600 °C. The phase transformed as the following process: H0.54Ti1.8650.135O4·0.5H2O ® H0.54Ti1.8650.135O4·0.25H2 ® H0.54Ti1.8650.135O4 ® TiO2(B) ® TiO2-anatase.